Pengaruh Pengetahuan, Sanksi, dan Tarif Terhadap Kepatuhan Wajib Pajak PBB-P2 - Virginia, Winda Ayu; Alimuddin, Irmawati (Owner : Riset dan Jurnal Akuntansi, 2024)
The research was conducted to determine the influence of knowledge, sanctions and tariffs on compliance with rural and urban land and building tax payers. This research was carried out at the Baubau City Dispenda because it has a strategic location and is one of the cities with quite high economic activity. The population in the study were all urban/rural land and building taxpayers. The sample used is the 2022 Baubau City Urban/Rural Land and Building Tax taxpayers. The sampling technique used is purposive sampling, that is, taxpayers are selected who come to pay the Urban/Rural Land and Building Tax at the Baubau City Bapenda office. Determination Withdrawal of samples using the slovin formula with a total of 90 respondents. The data analysis technique in this study is variant-based with the Partial Least Square (PLS) alternative using SmartPLS software. This research provides empirical evidence regarding taxpayer compliance in paying PBB-P2 in Baubau City and the following conclusions can be expressed: 1) Taxpayer knowledge has a significant effect on taxpayer compliance in paying PBB-P2; 2) Tax sanctions have a significant effect on taxpayer compliance in paying PBB-P2; 3) Tax rates have no significant effect on taxpayer compliance in paying PBB-P2. The Baubau City Government can continue to maintain existing policies such as the socialization of PBB-P2 and can also design policies so that paying off PBB-P2 becomes a condition for managing several licensing administrations which are the authority of the Baubau City Government.